A comparative analysis of Danionella cerebrum and zebrafish (Danio rerio) larval locomotor activity in a light-dark test - Lindemann, Nina; Kalix, Leon; Possiel, Jasmin; Stasch, Richard; Kusian, Tamia; Köster, Reinhard Wolfgang; von Trotha, Jakob William (Frontiers in Behavioral Neuroscience, 2022)
The genus Danionella comprises some of the smallest known vertebrate species and is evolutionary closely related to the zebrafish, Danio rerio. With its optical translucency, rich behavioral repertoire, and a brain volume of just 0.6 mm3, Danionella cerebrum (Dc) holds great promise for whole-brain in vivo imaging analyses with single cell resolution of higher cognitive functions in an adult vertebrate. Little is currently known, however, about the basic locomotor activity of adult and larval Danionella cerebrum and how it compares to the well-established zebrafish model system. Here, we provide a comparative developmental analysis of the larval locomotor activity of Dc and AB wildtype as well as crystal zebrafish in a light-dark test. We find similarities but also differences in both species, most notably a striking startle response of Dc following a sudden dark to light switch, whereas zebrafish respond most strongly to a sudden light to dark switch. We hypothesize that the different startle responses in both species may stem from their different natural habitats and could represent an opportunity to investigate how neural circuits evolve to evoke different behaviors in response to environmental stimuli.